Cardioprotective effect of miR-214 in myocardial ischemic postconditioning by down-regulation of hypoxia inducible factor 1, alpha subunit inhibitor - Wan, D-Y; Zhang, Z; Yang, H-H (Cellular and Molecular Biology, 2015)
To determine the significance of miR-214 expression in ischemic post-conditioning. Sixty rats were grouped to establish animal models. Immuno- luminescence and chemical methods were used to detect oxidative stress indicators. Hemodynamics indexes were measured by carotid artery intubation, and ischemia and infarction areas by Evans blue and 2,3-5 triphenyltetrazolium chloride(TTC) staining. TargetScan was used for identification and luciferase assays for verification of target genes.miR-214 and hypoxia inducible factor 1, alpha subunit inhibitor (HIF1AN) were analyzed by real-time quantitative polymerase chain reaction. Ischemia reperfusion significantly decreased left ventricular systolic pressure, +dp/dtmax, and -dp/dtmax and increased left ventricular end-diastolic pressure; ischemic post-conditioning had contrasting effects. Compared to the sham group, the ischemic/reperfusion (IR) group showed increased creatine kinase isoenzyme (CK-MB) and malondialdehyde (MDA) in the myocardium and decreased SOD. miR-214 in the IR group was down-regulated, and HIF1AN, up-regulated. Compared with the IR group, the ischemia postconditioning (IPC) group showed decreased CK-MB and MDA in the myocardium and increased SOD. The proportion of infarction area to ischemia area in IPC group declined compared to IR group. miR-214 and HIF1AN in the IPC group showed significant up- and down-regulation, respectively. Ischemic postconditioning can improve myocardial function, reduce myocardial infarction area, and prevent the ischemia reperfusion injury. miR-214 may participate in the protective function of ischemic post-conditioning by down-regulating HIF1AN.